The long-term impact of early life poverty on orbitofrontal cortex volume in adulthood: results from a prospective study over 25 years - Holz, Nathalie E.; Schmidt, Martin H.; Meyer-Lindenberg, Andreas; Banaschewski, Tobias; Brandeis, Daniel; Laucht, Manfred (Neuropsychopharmacology, 2014)
Converging evidence has highlighted the association between poverty and conduct disorder (CD) without specifying neurobiological pathways. Neuroimaging research has emphasized structural and functional alterations in the orbitofrontal cortex (OFC) as one key mechanism underlying this disorder. The present study aimed to clarify the long-term influence of early poverty on OFC volume and its association with CD symptoms in healthy participants of an epidemiological cohort study followed since birth. At age 25 years, voxel-based morphometry was applied to study brain volume differences. Poverty (0=non-exposed (N=134), 1=exposed (N=33)) and smoking during pregnancy were determined using a standardized parent interview, and information on maternal responsiveness was derived from videotaped mother-infant interactions at the age of 3 months. CD symptoms were assessed by diagnostic interview from 8 to 19 years of age. Information on life stress was acquired at each assessment and childhood maltreatment was measured using retrospective self-report at the age of 23 years. Analyses were adjusted for sex, parental psychopathology and delinquency, obstetric adversity, parental education, and current poverty. Individuals exposed to early life poverty exhibited a lower OFC volume. Moreover, we replicated previous findings of increased CD symptoms as a consequence of childhood poverty. This effect proved statistically mediated by OFC volume and exposure to life stress and smoking during pregnancy, but not by childhood maltreatment and maternal responsiveness. These findings underline the importance of studying the impact of early life adversity on brain alterations and highlight the need for programs to decrease income-related disparities.